Evaluation of the microbiological quality of aguamiel and pulque from San Agustín Tlaxiaca, Hidalgo, Mexico - Jaguey Hernández, Yari; Liborio Aldana, Guillermo Enrique; Castañeda Ovando , Araceli; Romo Gómez, Claudia; Contreras López, Elizabeth; Jaimez Ordaz, Judith; Tapia Ignacio, Cecilio (JOURNAL OF BASIC SCIENCES, 2024)
Pulque and aguamiel contain many microorganisms and compounds with prebiotic and probiotic properties that can enhance intestinal microbiota diversity. Despite the potential benefits, their consumption has decreased. This study aimed to evaluate the microbiological quality of aguamiel and pulque from San Agustín Tlaxiaca, Hidalgo. The study examined the presence of aerobic mesophiles, total coliforms, molds, and yeasts. In aguamiel, 1.8x103 CFU/mL of aerobic mesophiles and 6.5 NMP/100mL of total coliforms were found. In pulque, the aerobic mesophiles increased to 1.02x105 CFU/mL, without totals coliforms and 6.43x106 CFU/mL of molds and yeasts. The presence of Gram-bacilli and coccobacilli, molds, and yeasts were observed. Microbiological quality is determined by various factors; however, establishing good practices will allow obtaining pulque with a lower load of unwanted microorganisms.
Keywords: aguamiel; pulque; microbiological quality; gut microbiota